Pore Size Distribution Influence on Suction Properties of Calcareous Stones in Cultural Heritage: Experimental Data and Model Predictions - Giorgio Pia; Ludovica Casnedi; Ulrico Sanna (Advances in Materials Science and Engineering)
Water sorptivity symbolises an important property associated with the preservation of porous construction materials. The water movement into the microstructure is responsible for deterioration of different types of materials and consequently for the indoor comfort worsening. In this context, experimental sorptivity tests are incompatible, because they require large quantities of materials in order to statistically validate the results. Owing to these reasons, the development of analytical procedure for indirect sorptivity valuation from MIP data would be highly beneficial. In this work, an Intermingled Fractal Units’ model has been proposed to evaluate sorptivity coefficient of calcareous stones, mostly used in historical buildings of Cagliari, Sardinia. The results are compared with experimental data as well as with other two models found in the literature. IFU model better fits experimental data than the other two models, and it represents an important tool for estimating service life of porous building materials.